Breaking through barriers: the need for effective research to promote language‐concordant communication as a facilitator of equitable emergency care. Issue 1 (14th January 2022) - Gutman, Colleen K.; Lion, K. Casey; Fisher, Carla L.; Aronson, Paul L.; Patterson, Mary; Fernandez, Rosemarie
Abstract: Individuals with limited English proficiency (LEP) are at high risk for adverse outcomes in the US health care system. This is particularly true for patients with LEP seeking care in the emergency department (ED). Although professional language interpretation improves the quality of care for these patients, it remains underused. The dynamic, discontinuous nature of an ED visit poses distinct challenges and opportunities for providing equitable, high‐quality care for patients with LEP. Evidence‐based best practices for identifying patients with LEP and using professional interpretation are well described but inadequately implemented. There are few examples in the literature of rigorous interventions to improve quality of care and outcomes for patients with LEP. There is an urgent need for high‐quality research to improve communication with patients with LEP along the continuum of emergency care in order to achieve equity in outcomes.